Frequency Identification of a Feedback Hammerstein System. Issue 28 (2015) - Giri, F.; Ahmed-Ali, T.; Brouri, A.; Chaoui, F.Z.; Radouane, A.
Abstract: The problem of identifying feedback Hammerstein systems is addressed. As the system involves nonparametric linear dynamics a frequency identification method is developed based on the analysis of the system L2 -incremental stability. The identification method consists of an estimator of the nonlinearity parameters and another for the linear subsystem frequency gain. The system stability analysis motivates the use of periodic exciting inputs which are formally shown to ensure the consistency of all involved estimators.